2019
DOI: 10.1371/journal.pone.0216741
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic status (SES) and 30-day hospital readmissions for chronic obstructive pulmonary (COPD) disease: A population-based cohort study

Abstract: Background Patients with chronic obstructive pulmonary disease (COPD) are more likely to be readmitted than patients with other chronic medical conditions, yet knowledge regarding such readmissions is limited. We aimed to determine factors associated with readmission within 30 days of a COPD hospitalization or death with an emphasis on examining aspects of socioeconomic status and specific comorbidities. Methods A population-based cohort study was conducted using health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 30 publications
2
31
1
Order By: Relevance
“…Congestive heart failure (CHF) has been reported to be the most common readmission diagnosis after respiratory-based disease according to studies conducted in the United States, 8 , 9 and also one-fifth of COPD patients have been known to have unrecognized coexisting heart failure. 30 Unlike previous studies, 8 , 9 , 20 , 31 we reported that the cardiac reasons for readmission after AECOPD in Korea accounted for as little as 3% of patients. Nationwide data have shown that Korean COPD patients have a lower body mass index, lower comorbid hypertension and dyslipidaemia, which are known as risk factors for cardiac disease, and a lower prevalence of myocardial infarct than other races or ethnic groups.…”
Section: Discussioncontrasting
confidence: 72%
“…Congestive heart failure (CHF) has been reported to be the most common readmission diagnosis after respiratory-based disease according to studies conducted in the United States, 8 , 9 and also one-fifth of COPD patients have been known to have unrecognized coexisting heart failure. 30 Unlike previous studies, 8 , 9 , 20 , 31 we reported that the cardiac reasons for readmission after AECOPD in Korea accounted for as little as 3% of patients. Nationwide data have shown that Korean COPD patients have a lower body mass index, lower comorbid hypertension and dyslipidaemia, which are known as risk factors for cardiac disease, and a lower prevalence of myocardial infarct than other races or ethnic groups.…”
Section: Discussioncontrasting
confidence: 72%
“…Previous COPD and non-COPD hospitalisations in the previous year also significantly increased the risk for 30-day readmission by 53% to 56% and 60% to 64%, respectively [38,39]. Consistent with other studies, GOTO et al [31] found that frequent exacerbators (defined as two hospitalisations in the past year) BOTTLE [21] GERSHON [32] GOTO [31] JACOBS [35] SHARIF [44] SIMMERING [45] TZY-CHYI YU [48] Overall (I 2 =95.4%, p=0.000) had a 2.5-fold increase in odds of readmission compared to non-frequent exacerbators. Disease severity of COPD was also a risk factor for readmission and has been evaluated using different tools.…”
Section: Meta-analysis Resultssupporting
confidence: 57%
“…An emergency room visit in the previous 6 months (1 versus 0) was associated with increased readmission risk with OR 1.90 (95% CI 1.01-3.58) in the study by BASHIR et al [19] and OR 1.25 (95% CI 1.21-1.29) in the study by HAKIM et al [33]. The risk of readmission increased with a greater number of previous emergency [19,32]. Previous COPD and non-COPD hospitalisations in the previous year also significantly increased the risk for 30-day readmission by 53% to 56% and 60% to 64%, respectively [38,39].…”
Section: Meta-analysis Resultsmentioning
confidence: 84%
See 2 more Smart Citations